XII Commonwealth Games Sept 30 to Oct 9 Brisbane Australia 82. ([Brisbane, Qld.] : XII Commonwealth Games Australia (1982) Foundation Limited, 1982)
Features a photograph of a male archer taking aim with the bow pulled back. Two smaller photographs are at the lower right side beneath the titles, and show a man aiming a double barrelled shot gun, and a woman playing badminton.
"A spectacular of sport".
Catalogue record generated as part of a batch load.
Also available online
Keywords: Athletes -- Australia -- Posters